RELEVANSI KONSEP PENYUCIAN JIWA AL GHAZALI DALAM REKONSTRUKSI PENDIDIKAN KARAKTER DI ABAD KE-21 - Badiatul Munawaroh; Nur Masfufatul Izzah; Abdul Hakim; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
This study explores the relevance of Al-Ghazali’s concept of tazkiyatun nafs (purification of the soul) in 21st-century character education. The research focuses on how spiritual values such as muhasabah (self-reflection), mujahadah (self-control), and the habituation of noble character can address moral crises, weak self-regulation, and the negative impacts of digital technology on youth. Using a qualitative descriptive approach, the study emphasizes the integration of intellectual, emotional, and spiritual dimensions into character education curricula. Findings reveal that tazkiyatun nafs strengthens moral resilience, mental health, and helps shape a generation that is not only digitally competent but also morally upright and spiritually grounded. This concept is highly relevant as a contextual, practical, and adaptive strategy for modern character education.